Madness at the movies: prioritised movies for self-directed learning by medical students. (October 2014) - Wilson, Nick; Heath, Deb; Heath, Tim; Gallagher, Peter; Huthwaite, Mark
Objective: We aimed to systematically compile a list of 10 movies to facilitate self-directed learning in psychiatry by medical students. Method: The selected areas were those of the top five mental health conditions from the Global Burden of Disease 2010 study. The search strategy for movies covered an extensive range of sources (published literature and websites), followed by closer examination and critical viewing of a sample. Results: Out of a total of 503 potential movies that were identified, 23 were selected for viewing and more detailed critique. The final top 10 were: for depressive and anxiety disorders: Ordinary People (1980), Silver Linings Playbook (2012); for illicit drug use: Trainspotting (1996), Winter's Bone (2010), Rachel Getting Married (2008), Half Nelson (2006); for alcohol use disorders: Another Year (2010), Passion Fish (1992); and for schizophrenia: The Devil and Daniel Johnston (2006), and An Angel at My Table (1990). Conclusions: The final selection of 10 movies all appeared to have relatively high entertainment value together with rich content in terms of psychiatric themes. Further research could evaluate the extent to which medical students actually watch such movies, by assessing the level of withdrawals from a medical school library and surveying student responses.